Recent Studies on Neoechinorhynchus curemai Noronha, 1973 (Acanthocephala: Neoechinorhynchidae), in Prochilodus lineatus Valenciennes, 1836, from Volta Grande Reservoir, MG, Brazil - MARTINS, M. L. [UNESP]; FUJIMOTO, R. Y. [UNESP]; ANDRADE, P. M. [UNESP]; TAVARES-DIAS, M. [UNESP] (Instituto Internacional de Ecologia, 2000)
O presente trabalho estudou a helmintofauna do curimbatá, Prochilodus lineatus Valenciennes, 1836, do reservatório de Volta Grande, MG, Brasil. Foram analisados 18 peixes com comprimento médio de 46,7 ± 1,1 cm e peso médio de 1.674,8 ± 75,6 g, sendo que 15 apresentaram acantocéfalos no intestino com prevalência de 83,3%. O helminto foi identificado como Neoechinorhynchus curemai Noronha, 1973 (Acanthocephala: Neoechinorhynchidae), que diferiu das outras espécies descritas pelas dimensões dos caracteres e pela morfologia. da descrição original de N. curemai difere pelas maiores dimensões dos testículos, pela glândula de cimento alongada, pela presença de núcleos nos lemniscos, pelas dimensões dos ovos e pelos maiores ganchos da probóscide presentes na segunda e na terceira fileiras nos machos e na primeira fileira nas fêmeas. Foi observada menor porcentagem ocupada pelo sistema reprodutivo em relação ao tronco da fêmea. A observação dos parátipos de N. curemai de Noronha (1973) mostrou grande semelhança com os do presente trabalho. Este fato complementa a descrição do helminto em outra localidade.

The present work described helminth parasites of curimbatá, Prochilodus lineatus Valenciennes, 1836 from Volta Grande Reservoir, MG, Brazil. Eighteen fishes with average 46.7 ± 1.1 cm length and 1,674.8 ± 75.6 g weight were collected. of the analysed fishes, 15 were parasitized with acanthocephalans in the intestine, showing a prevalence of 83.3%. The helminth was identified as Neoechinorhynchus curemai Noronha, 1973 (Acanthocephala: Neoechinorhynchidae). It differs from other species in dimension of characters and morphology. From the original description of N. curemai, it differs from the biggest dimension of testis, elongated cement gland, nucleated lemnisci, eggs size, larger proboscis hooks length in the middle and in the third circle in males and larger hooks in the anterior circle in females. A smaller percentage occupied by the reproductive system in female trunk was reported. The observation of paratypes of N. curemai of Noronha (1973) showed a great similarity with those of the present work. This fact complements the helminth description from elsewhere.
Estudos recentes sobre Neoechinorhynchus curemai Noronha, 1973 (Acanthocephala: Neoechinorhynchidae), em Prochilodus lineatus Valenciennes, 1836, do Reservatório de Volta Grande, MG, Brasil
Keywords: Acanthocephala; Neoechinorhynchus curemai; Prochilodus lineatus; Minas Gerais; Brasil; Acanthocephala; Neoechinorhynchus curemai; Prochilodus lineatus; Minas Gerais; Brazil